Isolation of Bacillus subtilis from Several Locations in Mataram and its Toxicity to Aedes aegypti Mosquitoes in the Laboratory - Alya Supriyani; Laila Annisa Rahmah; Sarkono Sarkono; Galuh Tresnani; Bambang Fajar Suryadi (University of Mataram, 2025)
One way to biologically control mosquitoes is by utilizing bacteria. Bacillus thuringiensis and Bacillus sphaericus are commonly used bacteria for this purpose. However, Bacillus subtilis has recently attracted the attention of researchers, as it is reported to have potential for use as a biopesticide. In this study, B. subtilis was isolated from several habitats in Mataram and West Lombok and tested on Aedes aegypti larvae to determine its potential toxicity. B. subtilis was isolated from the soil using a heating technique to separate it from other bacteria that do not have endospores and then grown at 33oC for 24 hours. The bacteria that grew were then tested on third-instar Ae. aegypti larvae. From several sampled locations, eight B. subtilis isolates with low toxicity levels were obtained. Toxic B. subtilis isolates were obtained from garden soil (isolate LT2C, 20%) and rhizosphere soil (isolate LB1A, 30%). The toxicity obtained is lower than the toxicity of B. thuringiensis and B. sphaericus, therefore further exploration is needed to be able to utilize B. subtilis as a biopesticide agent.